What is Non-Market (Strategy)? - Faria, Alexandre de Almeida; Abdalla, Márcio Abdalla Moutinho (Organizações & Sociedade, 2014)
The area of strategic management (SM) brings an increasing number of challenges and opportunities for academics and strategists of the rest of world. Because of the increasing importance of the rest of the world in the context of neoliberal globalization, the concept of non-market in SM had a surprising and curious trajectory of rise in recent years, after a long period of marginalization during the Cold War. From the perspective of the rest of the world, this paper reviews the concept of non-market through a historical and interdisciplinary perspective which challenges the underlying market theory and brings to surface geopolitical dimensions of knowledge to explain the curious trajectory of the non-market concept in SM. Analysis shows that non-market is a concept that enables large corporations to intervene in the rest of the world through so-called non-market strategies which are legitimized as necessary evil. Through a perspective of multipolar dialogue, the authors propose the reconceptualization of non-market and non-market strategy in Brazil through the engagement with market theories that have been marginalized by americanism.